THE INFLUENCE OF COMPENSATION AND VILLAGE GOVERNMENT SUPPORT ON THE PERFORMANCE OF OPERATIONAL IMPLEMENTERS WITH WORK MOTIVATION AS A MEDIATING VARIABLE AT BUMDES IN BELITUNG DISTRICT: THE INFLUENCE OF COMPENSATION AND VILLAGE GOVERNMENT SUPPORT ON THE PERFORMANCE OF OPERATIONAL IMPLEMENTERS WITH WORK MOTIVATION AS A MEDIATING VARIABLE AT BUMDES IN BELITUNG DISTRICT - Maryani, Yayan; Yusuf, M.; Nuraeni, Nuraeni; Hasanah, Hasanah (PENANOMICS: International Journal of Economics, 2024)
This study is to find out and analyze the influence of compensation and support of the village government on the performance of operational implementers with work motivation as a mediating variable in BUMDes in Kabupaten Belitung. In this study, the method used is an associative method with a quantitative approach. Meanwhile, the number of samples used was 78 respondents from operational implementation personnel at BUMDes in Kabupaten Belitung, with a sampling technique, namely random sampling. Then in this study, the analysis method used is SEM-PLS. The results of this study are (1) that compensation has a positive and significant effect on work motivation, (2) that village government support has a positive and significant effect on motivation, (3) that compensation has a positive and significant effect on performance, (4) that village government support has a positive and significant effect on performance, (5) that motivation has a positive and significant effect on performance, (6) that compensation has a non-significant effect on employee performance through motivation, and (7) that the support of the village government has a positive and significant effect on performance through work motivation.